Detection of High Local Groundwater Inflow to Rock Tunnels using ASTER Satellite Images - M. Sharafi; S. Khazaei (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
High local groundwater flow into rock tunnels may lead to a potential hazard and is an important factor influencing construction time and costs. Geological features such as fault zones and open fractures can be the source of very high local groundwater inflows. Having a reliable estimation of location groundwater inflows is essential before excavation of tunnels. To reduce the costs and time of field works, remote sensing investigations can be a good solution. The main aim of the present study is to propose a methodology for detecting the geomorphic markers of cuesta in the high local groundwater inflow to Nosoud tunnel using the satellite imagery data. For this purpose, a reflectance image from the ASTER satellite sensor was used. Our Experiments show that cuesta springs, caused by hydraulic fracturing, can be detected using the normalized difference vegetation index (NDVI) map, computed on the ASTER image, and analyzing the topographic and morphometric features of the area. Moreover, observations in tunnel excavation stage showed that crossing through open fractures in hard and thick layers is the major cause of water inflow into the tunnel, which corresponds to the surface hydrogeological evidences obtained from the ASTER image.